Zwölf Jahre Personalbefragung im Schweizer Justizvollzug - Young, Christopher; Mangold, Conor (Über Mauern blicken - 25 Jahre Forschen im Justizvollzug: Festschrift für Ueli Hostettler zum 65. Geburtstag, 2025)
Over the past twelve years, various staff surveys have been conducted in the Swiss prison system under the direction of Ueli Hostettler (2012, 2017, 2020, 2023). This article provides an overview of the history and methodology of these surveys. Between 37 and 49 percent of employees in the Swiss prison system took part in each survey. Selected results are presented and the development of some work-related attitudes is examined. The surveys showed that job satisfaction remained stable at a high level in all survey years. More than three-quarters of respondents were satisfied. Compared to the first survey in 2012, satisfaction was slightly lower in 2023 and in the other survey years. Similarly, around half expressed a high level of commitment and around two-thirds expressed a high level of satisfaction with the cooperation with their direct superiors. There were some differences between the concordats in terms of commitment and cooperation with supervisors, particularly between the two German-speaking concordats and the concordat in Latin Switzerland, where commitment and satisfaction with cooperation with direct supervisors were rated slightly less positively. (machine translation)